MATHEMATICS AND PHYSICS ESTIMATES OF SLOW CONTROLS - Carja, O.; Lazu, A. I. (European Scientific Journal, ESJ, 2014)
We consider a linear control system with the origin as target and study the behavior of the minimum norm control as time duration goes to infinity